Students’ Needs for Culturally Responsive English Teaching Materials: Integrating Multicultural Content, Universal Values, and Local Wisdom - Kuzairi; Ali Wafa (English Department, Universitas Negeri Surabaya, 2025)
This study aims to analyze the needs of students regarding the development of English teaching materials that integrate multicultural content, universal values, and local wisdom. A quantitative descriptive research design was employed, with data collected through a questionnaire administered to 30 students in grades VII and VIII of Junior High School. The questionnaire consisted of 25 items covering five dimensions: the importance of English, multicultural content, universal values, local wisdom, and media and learning methods. Data were analyzed using descriptive statistics. The results reveal consistently high ratings, with the themes “Importance of English” mean score is 4.28, “Contextual and Multicultural” (4.01), “Universal Values” (4.39), “Local Wisdom” (4.22), and “Media & Methods” 4.19). Therefore, it indicates strong student support for integrating local Probolinggo/Tengger cultural elements (e.g., Kasada Ceremony, Bromo tourism) into English materials. Students also emphasized the importance of universal values such as honesty, cooperation, and tolerance, as well as interactive and multimedia-based learning approaches. These findings serve as a pedagogical implication for developing contextual, engaging, and character-building English teaching materials tailored to students’ needs and cultural backgrounds.